The Effect of Reciprocal Teaching Style on Pencak Silat Side Kick Learning Outcomes - Keliat, Pedomanta; Karo-Karo, Alan Alfiansyah Putra; Muhammad Syaleh (Jurnal Pendidikan Jasmani (JPJ), 2020)
This study aims to find out how to improve the learning outcomes of the side kick by using the application of reciprocal teaching styles to class X students of Hang Tuah High School in the academic year 2015/2016. When the research was conducted in January 2016. Based on student learning outcomes in the pre-test after the first learning achievement test, it can be seen that the initial ability of students in doing Side Kick techniques is still low. From 30 students there are 20 people (67%) who have achieved mastery learning, while 10 people (33%) have not reached mastery learning. With an average value of student learning outcomes is 76. Whereas in the pre-testI can be seen that the ability of students to test the results of learning classically has increased. Of the 30 students there were 26 people (87%) who had achieved mastery learning, while 4 people (13%) had not reached mastery learning. With an average value of student learning outcomes is 80. Based on this it can be concluded that learning through the application of reciprocal teaching styles can improve learning outcomes of side kicks in class X students of Hang Tuah Belawan High School in the academic year 2015/2016.